Implementasi Program Pengentasan Kemiskinan di Desa Dawuhan Kidul Kabupaten Kediri - Ermai Dwi Wandasari; Yusuf Hariyoko; Wahid Hidayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Poverty remains a persistent social issue and a major challenge in development, prompting the government to implement various social assistance programs as poverty alleviation efforts. However, the success of a program depends not only on policy formulation but also on its implementation in the field. This study aims to analyze the implementation of poverty alleviation programs in Dawuhan Kidul Village, Kediri Regency. Using a descriptive qualitative method, this study applies the policy implementation framework by Van Meter and Van Horn, which encompasses policy standards and objectives, resources, characteristics of the implementing agency, disposition of implementers, inter-organizational communication and enforcement activities, as well as the economic, social, and political environment. Data were gathered through interviews, observation, and documentation, and subsequently analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of poverty alleviation initiatives—including the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), food aid, and other social welfare schemes—has successfully helped residents meet their basic needs. Program execution is supported by coordination among implementers, available supporting facilities, and well-maintained communication between the village government, social assistants, and the community. Nevertheless, several bottlenecks remain, such as inaccurate targeting of beneficiaries, limited data updates, delayed distribution information, and social jealousy within the community. Furthermore, the village government's limited authority in selecting beneficiaries hinders the optimal resolution of emerging issues at the local level. In conclusion, while the implementation of poverty alleviation programs in Dawuhan Kidul Village has been reasonably effective, improvements are urgently required regarding data accuracy, inter-agency coordination, and the optimization of the village government's local authority.